Complement Inhibition as a Proposed Neuroprotective Strategy following Cardiac Arrest - Brad E. Zacharia; Zachary L. Hickman; Bartosz T. Grobelny; Peter A. DeRosa; Andrew F. Ducruet; E. Sander Connolly (Mediators of Inflammation)
Out-of-hospital cardiac arrest (OHCA) is a devastating disease process with neurological injury accounting for a disproportionate amount of the morbidity and mortality following return of spontaneous circulation. A dearth of effective treatment strategies exists for global cerebral ischemia-reperfusion (GCI/R) injury following successful resuscitation from OHCA. Emerging preclinical as well as recent human clinical evidence suggests that activation of the complement cascade plays a critical role in the pathogenesis of GCI/R injury following OHCA. In addition, it is well established that complement inhibition improves outcome in both global and focal models of brain ischemia. Due to the profound impact of GCI/R injury following OHCA, and the relative lack of effective neuroprotective strategies for this pathologic process, complement inhibition provides an exciting opportunity to augment existing treatments to improve patient outcomes. To this end, this paper will explore the pathophysiology of complement-mediated GCI/R injury following OHCA.